The quantum harmonic oscillator expected shortfall model; El modelo de déficit esperado basado en el oscilador armónico cuántic - Vladimir M. Markovic; Nikola Radivojevic; Tatjana Ivanovic; Slobodan Radisic; Nenad Novakovic (Estudios de Economía, 2023)
This paper presents a new Expected Shortfall (ES) model based on the Quantum Harmonic Oscillator (QHO). It is used to estimate market risk in banks and other financial institutions according to Basel III standard. Predictions of the model agree with the empirical data which displays deviations from normality. Using backtesting, it is shown that the model can be reliably used to assess market risk.
Keywords: G24; C22; C52; C53; 330; Expected Shortfall; market risk; Basel III standard; stock returns; S&P index